Penerapan Model Pembelajaran Team Games Tournament Berbantuan Media Kartu Misteri Untuk Meningkatkan Keterampilan Sosial Siswa - Bahri, Syaiful (Science and Education Journal (SICEDU), 2025)
This research is motivated by the low social skills of students in VA classes. This research aims to improve students' social skills by applying a cooperative learning model of the Team Games Tournament (TGT) type in VA students of UPT SDN 009 Sendayan. This research is a classroom action research (PTK), which is carried out in two cycles and each cycle consists of two meetings. The subjects in this study are all VA class students totaling 20 students. Data collection techniques are in the form of observation and documentation techniques. Meanwhile, the data analysis technique used is a combination of qualitative data and quantitative data. Based on the results of the research that has been carried out through 2 cycles, in the 1st meeting of the first cycle of students who completed there were 10 students with a percentage of 50% with an overall average of 65.75 and in meeting 2 it increased to 13 students with a percentage of 65% with an overall average of 70.25. Meanwhile, in the second cycle of meeting 1 students who completed there were 15 students with a percentage of 75% with an overall average of 76.25 and there was an increase in meeting 2 to 17 students with a percentage of 85% with an overall average of 80.25. Based on the results of this study, it shows that by applying the Team Games Tournament (TGT) learning model, it can improve the social skills of grade 5A students of UPT SDN 009 Sendayan.